AUTISM SPECTRUM DISORDER: BEHAVIORAL AND GENETIC ASPECTS - Pereira, André Marcelo Lima; Liberato, Pedro Henrique da Silva; Elsenbach, Djefferson; de Oliveira, Rafael Alves; Covizzi, Júlia Vilas Boas; Bôas, João Renato Villas; Morandim, Lígia Lima; Covizzi, Ian Vilas Boas; de Oliveira, Jessica Gisleine; Lima, Alba Regina de Abreu; Covizzi, Uderlei Doniseti Silveira (Seven Editora, 2026)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by persistent deficits in communication and social interaction, associated with restricted and repetitive patterns of behavior, interests, or activities. This study aims to present a review of the main conceptual, clinical, and genetic aspects related to autism, highlighting scientific advances that have contributed to a broader understanding of the disorder. Over time, the conception of autism has undergone important changes, and it is currently understood as a spectrum that involves different levels of manifestation and need for support. Clinically, ASD manifests itself from early childhood and may include difficulties in verbal and nonverbal communication, impairments in social interaction, stereotyped behaviors, restricted interests, and sensory alterations. Early identification of the disorder is considered fundamental, as it allows for more effective therapeutic interventions and favors better outcomes in the cognitive, social, and communicative development of the individual. In the field of genetics, recent research indicates that ASD has a strong hereditary component, involving multiple genes associated with the development and functioning of the nervous system. Rare and common genetic variants, spontaneous mutations, and epigenetic alterations contribute to the clinical heterogeneity observed among individuals on the spectrum. Furthermore, environmental factors can interact with genetic predisposition, influencing the risk of developing the disorder. Therefore, ASD should be understood as a multifactorial and complex condition, whose continuous investigation is essential to expand knowledge about its biological mechanisms, improve diagnostic strategies, and develop more effective therapeutic interventions.